Optimizing Library Management through SLiMS Application: A Case Study at Jalaluddin Ar Rumi Junior High School - Baba Rahim, Norizan; Danil, Mohammad; Miliani, Masyrisal (CV Media Inti Teknologi, 2025)
Background of Study: Digital transformation in library management has become increasingly essential, especially for educational institutions with limited resources. The Senayan Library Management System (SLiMS), as an open-source application, offers a cost-effective alternative to replace manual systems efficiently. SMP Plus Jalaluddin Ar Rumi is one of the schools adopting SLiMS to improve the quality of its library services. Aims and Scope of Paper: This study aims to describe the implementation of the SLiMS application in managing library collections and circulation services. The scope covers cataloging processes, classification, loan-return services, and user access to the digital catalog (OPAC). Methods: This research adopts a qualitative descriptive approach using non-participant observation techniques. Data were collected through direct observation of library activities and documentation from the SLiMS system over a four-week period. Thematic analysis was used to identify key patterns from the observations. Result: The findings show that SLiMS improves the efficiency of bibliographic data entry, accelerates circulation services, and enhances information access through the OPAC feature. The system supports real-time transaction management and generates useful statistical reports. Furthermore, student interaction with the system contributes to the development of digital literacy skills. Conclusion: The implementation of SLiMS at SMP Plus Jalaluddin Ar Rumi has a positive impact on the efficiency of library services and the quality of information access. The system not only replaces manual processes but also plays a key role in modernizing school libraries to align with the digital era.